PENGARUH PROBLEM BASED LEARNING BERBANTUAN STRATEGI PIPIZ (PEGAWAI PIZZA) TERHADAP KETEPATAN MENGOLAH KONSEP DASAR OPTIKA GEOMETRIS - Bundy Putera Adyatama; Nur Khoiri; Harto Nuroso (Jurnal Penelitian Pembelajaran Fisika, 2015)
The purpose of this study was to determine the effect of student learning outcomes that gained model of problem based learning assisted by PIPIZ ( Employees Pizza ) strategy and the learning outcomes of students who get a problem based learning model without assisted by PIPIZ  ( Employee Pizza ) against precison of basic processing concepts in geometrical optics materials , In addition to know the differences in learning outcomes of students who get a problem based learning model assisted by PIPIZ ( Employee Pizza ) strategy and the learning outcomes of students who get a model problem based learning without assisted by PIPIZ  ( Employee Pizza ) against precison of basic processing concepts in geometrical optics materials in Kesatrian 1 Semarang senior high school grade X school year 2014/2015.This study using Nonequivalent Control Group Design method this design is similar to the pretest-posttest control group design comparing experimental class and control class. The population in this study is grade X MIA in Kesatrian 1 Semarang senior high school, amounting to 6 classes the number of students 210 people. This research sample selected by random cluster sampling method, where classes were randomly selected and selected sample is a class X MIA 1 and X MIA 4.The results showed that the student of grade X Kesatrian 1 Semarang senior high school on geometric optics subjects taught by teaching using problem based learning model assisted by PIPIZ  (Employee Pizza) strategy (experimental class) gained an average value of  7.65. While the results of student in grade X  Kesatrian 1 Semarang senior high school on geometric optics subjects taught by learning using a model of problem based learning without assisted by PIPIZ  (Employee Pizza) strategy (control class) gained an average value of 64. The results of the study can be interpreted that the learning outcomes of students who get a model problem based learning assisted by PIPIZ (Employee Pizza) strategy is better than learning outcomes of students who get a model problem based learning without assisted by PIPIZ (Employee Pizza) strategy against precison of basic processing concepts. There are differences in learning outcomes of students of class X  Kesatrian 1 Semarang senior high school on geometric optics material taught by learning using a model of problem based learning assisted by PIPIZ (Employee Pizza) strategy and taught by learning using a model of problem based learning without assisted by PIPIZ (Employee Pizza) strategy. The difference is shown by the price of  with significance level of 5% (3.472> 1.67).